One electron oxygen reduction in room temperature ionic liquids: A comparative study of Butler-Volmer and Symmetric Marcus-Hush theories using microdisc electrodes - Tanner, E; Xiong, L; Barnes, E; Compton, R (Elsevier, 2014)
The voltammetry for the reduction of oxygen at a microdisc electrode is reported in two room temperature ionic liquids: 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl) imide ([Bmpyrr][NTf2]) and trihexyltetradecylphosphonium bis(trifluoromethylsulfonyl) imide ([P 14,6,6,6][NTf2]) at 298 K. Simulated voltammograms using Butler-Volmer theory and Symmetric Marcus-Hush (SMH) theory were compared with experimental data. Butler-Volmer theory consistently provided experimental parameters with a higher level of certainty than SMH theory. A value of solvent reorganisation energy for oxygen reduction in ionic liquids was inferred for the first time as 0.4-0.5 eV, which is attributable to inner-sphere reorganisation with a negligible contribution from solvent reorganisation. The developed Butler-Volmer and Symmetric Marcus-Hush programs are also used to theoretically study the possibility of kinetically limited steady state currents, and to establish an approximate equivalence relationship between microdisc electrodes and spherical electrodes resting on a surface for steady state voltammetry for both Butler-Volmer and Symmetric Marcus-Hush theory. © 2014 Elsevier B.V. All rights reserved.